The Role of Human Resources in Landscaping Construction - Wang, Feng’e (Journal of Theory and Practice of Management Science, 2023)
Under the basic situation of rapid social development, economic level and people's material living standard constantlyrising,environmental problems have become increasingly prominent. Through change and development these years, haze phenomenon can besaid to be relatively common in our country, which has caused serious impact on People's Daily life. In order to promote our socialeconomy to get better development, in order to ensure people's health, strengthen the greening projects, then, this paper inview of humanresources in the landscape construction role of the detailed discussion, in view of some common problems proposed concrete improvementmeasures, hope to promote the role of human resources in the greening engineering projects to get adequate play, promote thegarden The rapid development of forest greening.